2001
DOI: 10.1046/j.1523-5378.2001.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

T Cell‐Mediated Cytotoxicity via Fas/Fas Ligand Signaling in Helicobacter pylori‐Infected Gastric Corpus

Abstract: T cell-mediated cytotoxicity via Fas/Fas-L signaling may contribute to the induction of apoptosis in gastric epithelial cells during H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
(66 reference statements)
2
8
1
Order By: Relevance
“…Specific IFN-γ-dependent induction of CD4+ T cell apoptosis may restrain inflammation (26), suggesting that IFN-γ maintains T cell homeostasis during immune responses. In H. felis -infected IFN-γ mice, apoptosis of CD4+ T cells appeared to be Fas-dependent, confirming prior reports (35, 36). Apoptosis of CD4+ T cells resulted in a reduction in Th1 and Th17 immune responses without a major change in Th2 responses, despite elevated IL-10 in H. felis infected IFN-γ mice, a cytokine milieu that has previously been shown to suppress inflammation-induced cancer in the gut (37).…”
Section: Discussionsupporting
confidence: 90%
“…Specific IFN-γ-dependent induction of CD4+ T cell apoptosis may restrain inflammation (26), suggesting that IFN-γ maintains T cell homeostasis during immune responses. In H. felis -infected IFN-γ mice, apoptosis of CD4+ T cells appeared to be Fas-dependent, confirming prior reports (35, 36). Apoptosis of CD4+ T cells resulted in a reduction in Th1 and Th17 immune responses without a major change in Th2 responses, despite elevated IL-10 in H. felis infected IFN-γ mice, a cytokine milieu that has previously been shown to suppress inflammation-induced cancer in the gut (37).…”
Section: Discussionsupporting
confidence: 90%
“…A similar correlation concerning differences in the expression of Fas ligand in the stomach wall was observed by Ishihara et al [5] As shown by their findings, positive FasL expression in the gastric mucosa associated with the presence of Helicobacter pylori infection occurs only in glandular epithelial cells, not in the lining epithelium.…”
Section: Discussionsupporting
confidence: 85%
“…21,22 CD8 þ T and NK cells utilize the Fas/FasL pathway to induce cellular lysis and injury in a variety of scenarios. 23,24 The indirect evidence provided by this series of studies as well as the findings in the present study provide rationale to investigate the ischemic component of CLP-induced pathology and the contributions of CD8 þ T and NK cells to this potential mechanism of injury.…”
Section: Discussionmentioning
confidence: 63%